(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
folk songs are the main part of Uzbek folklore. People’s dreams, goals, and pains are glorified in them. The place of faunistic images in reflecting the artistic landscape of the world is incomparable. This article talks about animal images that appear in folk lyrics. Based on the ancient Turkic worldview, the people’s belief in them is illustrated in the examples. The use of faunistic images in various symbolic meanings is proved by a number of poetic passages.